Model to Predict Polymer Fibre Diameter during Melt Spinning - Alexander M. Bier; Michael Redel; Dirk W. Schubert (Advances in Polymer Technology)
Polymeric materials were evaluated with regard to their spinnability and respective fibre diameters. A modified single fibre spinning device was firstly used to derive a novel generalised model, utilising process parameters (die diameter, throughput, and stretching relevant take-up pressures) and material properties (zero shear viscosity) to predict the diameter of polymeric fibres on the basis of four different polymers. Further evaluation of the resulting power law dependence was conducted on filaments produced via conventional melt spinning and meltblown processes. Fibres produced on the pilot machines showed close agreement with the model equation with only the need to adjust an easily calculable device dependent factor. The outcome of the presented work is a user-friendly model of high practical relevance, which can be used to predict the diameter of amorphous and semicrystalline polymeric fibres, independent of material and machine used with sufficient accuracy for fast estimations.